2012
DOI: 10.3748/wjg.v18.i10.1028
|View full text |Cite
|
Sign up to set email alerts
|

15-PGDH is reduced and induces apoptosis and cell cycle arrest in gastric carcinoma

Abstract: Reduction of 15-PGDH is associated with carcinogenesis and development of gastric carcinoma. 15-PGDH induces apoptosis and cell cycle arrest in SGC-7901 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Yoo et al [36] and Jang et al [37] reported that 15-PGDH expression did not differ between gastric cancer tissue and normal tissue. However Liu et al [38], Tatsuwaki et al [39], Lou et al [40] and Song et al [25] asserted that 15-PGDH expression was decreased in 50e100% of cases of gastric cancer. Jang et al [37] and Thiel et al [35] used Western blot analysis to show that 15-PGDH expression was reduced.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Yoo et al [36] and Jang et al [37] reported that 15-PGDH expression did not differ between gastric cancer tissue and normal tissue. However Liu et al [38], Tatsuwaki et al [39], Lou et al [40] and Song et al [25] asserted that 15-PGDH expression was decreased in 50e100% of cases of gastric cancer. Jang et al [37] and Thiel et al [35] used Western blot analysis to show that 15-PGDH expression was reduced.…”
Section: Discussionmentioning
confidence: 96%
“…Tatsuwaki et al [39] asserted that 15-PGDH was unrelated to the depth of invasion or degree of lymph node metastasis, but was related to the degree of differentiation and stage. Lou et al [40] mentioned that 15-PGDH was associated with pathologic type, TNM stage and distant metastasis, but not cancer location and size. As reported in most studies, we also found that 15-PGDH expression was not related to age and gender but was related to pathologic type, T stage, N stage and TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of 15-PGDH was reduced in microdissected early hyperplasic lesions and in colorectal carcinomas suggesting that 15-PGDH plays a role in prevention of tumor progression (Ding, Tong, 2005, Lou, Jing, 2012, Mann, Backlund, 2006.…”
Section: Several Lines Of Evidence Suggest That Cox-2 Signaling Is Immentioning
confidence: 99%
“…The third enzyme involved in PGE 2 homeostasis, 15-PGDH, also plays an important role in carcinogenesis. 15-PGDH is downregulated and is a tumor suppressor in gastrointestinal, breast and lung cancers (Ding, Tong, 2005, Lou et al , 2012, Wolf, O'Kelly, 2006, Yan, Rerko, 2004. 15-PGDH catalyzes the rate 14 limiting step of PG catabolism and thus represents a physiological antagonist of COX-2 (Backlund et al , 2005).…”
Section: Several Lines Of Evidence Suggest That Cox-2 Signaling Is Immentioning
confidence: 99%
“…The SGC-7901 cell line was cultured in an RPMI 1640 medium (Sigma, St. Louis, MO) supplemented with 100 U/mL penicillin, 100 mg/mL streptomycin, and 10% heat inactivated fetal calf serum (Sijiqing, Hangzhou, China). The cells were grown under saturated humidity conditions at 37 C and 5% CO 2 (Lou et al, 2012).…”
Section: Cell Culturementioning
confidence: 99%